Sequential Delivery of Dual Growth Factors from Injectable Chitosan-Based Composite Hydrogels - Qing Min; Jiaoyan Liu; Xiaofeng Yu; Yuchen Zhang; Jiliang Wu; Ying Wan (Marine Drugs, 2019)
Local administration of platelet-derived growth factor-BB (PGDF-BB) and bone morphogenetic protein-2 (BMP-2) in a sequential release manner could substantially promote bone healing. To achieve this goal, a delivery system that could sustain the release of PGDF-BB and BMP-2 by way of temporal separation was developed. One type of PGDF-BB-encapsulated alginate microsphere and another type of BMP-2-encapsulated microsphere with a core-shell structure were respectively produced using emulsification methods. These two types of microspheres were then embedded into chitosan/glycerophosphate hydrogel for constructing composite gels. Some of them were found to be injectable at ambient temperature and had thermo-sensitive features near physiological temperature and pH. The optimally formulated composite gels showed the ability to control the release of PGDF-BB and BMP-2 in a sequential fashion in which PDGF-BB was released earlier than BMP-2. In vitro release patterns indicated that the release rates could be significantly regulated by varying the embedded amount of the factor-encapsulated microspheres, which can in turn mediate the temporal separation release interval between PGDF-BB and BMP-2. The released PDGF-BB and BMP-2 were detected to be bioactive based on their respective effects on Balb/c 3T3 and C2C12 cells. These results suggest that the presently developed composite gels have the potential for bone repair by synergistically utilizing the early chemotactic effect of PDGF-BB and the subsequent osteogenic and angiogenic functions of PDGF-BB and BMP-2.